2012
DOI: 10.1152/ajpheart.00340.2011
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of 20-HETE inhibition in a model of oxygen-glucose deprivation in hippocampal slice cultures

Abstract: Recent studies have indicated that inhibitors of the synthesis of 20-hydroxyeicosatetraenoic acid (20-HETE) may have direct neuroprotective actions since they reduce infarct volume after ischemia reperfusion in the brain without altering blood flow. To explore this possibility, the present study used organotypic hippocampal slice cultures subjected to oxygen-glucose deprivation (OGD) and reoxygenation to examine whether 20-HETE is released by organotypic hippocampal slices after OGD and whether it contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 43 publications
4
49
0
Order By: Relevance
“…26,31 In other studies, 20-HETE inhibition reduced lesion volume and neurodegeneration independent of CBF, suggesting a direct neuroprotective effect of 20-HETE inhibition. 17,18,32 In a global cerebral ischemia model in immature piglets similar in some ways to our model, Yang et al 17 showed direct neuroprotection after CA in piglets treated with HET0016. In that report, focal cortical CBF measured by laser Doppler was not affected by treatment with HET0016 at 5 minutes after resuscitation.…”
Section: Discussionsupporting
confidence: 67%
“…26,31 In other studies, 20-HETE inhibition reduced lesion volume and neurodegeneration independent of CBF, suggesting a direct neuroprotective effect of 20-HETE inhibition. 17,18,32 In a global cerebral ischemia model in immature piglets similar in some ways to our model, Yang et al 17 showed direct neuroprotection after CA in piglets treated with HET0016. In that report, focal cortical CBF measured by laser Doppler was not affected by treatment with HET0016 at 5 minutes after resuscitation.…”
Section: Discussionsupporting
confidence: 67%
“…ND, not detected. Recent studies reported that CYP4A immunoreactivity was detected in neurons in hippocampus and putamen (Renic et al, 2012;Yang et al, 2012). In this study, CYP4A immunoreactivity was also detected in neurons in contralateral cortex and striatum.…”
Section: Discussionsupporting
confidence: 67%
“…Inhibition of 20-HETE not only reduces infarct size, but also improves neurological outcomes in MCAO models (Dunn et al, 2008; Renic et al, 2009). Blockade of 20-HETE synthesis alleviated neuronal cell death in brain slices subjected to oxygen and glucose deprivation in association with decreased superoxide production and caspase-3 activation (Renic et al, 2012). The neuroprotective effect of 20-HETE inhibition could be explained by amelioration of inflammation, as well as oxidative stress, by diminishing recruitment of leukocytes, decreasing production of IL-1, IL-6, chemokine (C-C motif) ligand 2 (CCL2) (aka monocyte chemoattractant protein-1 (MCP-1)), interferon gamma (IFN-γ), TNF-α, and reducing expression of ICAM-1 and VCAM-1 on B-lymphocytes and endothelium (Shekhar et al, 2017a; Toth et al, 2013).…”
Section: Recently Identified Molecular/cellular Targets and Approachesmentioning
confidence: 99%